Women's participation in politics: Momentum for change in Dompu District - Firdiansyah, Muhammad Ardi (Universitas Islam Malang, 2024)
Since the implementation of direct regional head elections (Pilkada) in 2004, the participation of women as candidates, both for the election of governors, regents, mayors and deputies, is still very minimal. In the 2005 and 2010 regional elections, only 26 women were elected. In 2015, of 1,646 eligible candidates, only 123 or 7.47% were women. In 2017, the number of women as candidates decreased to 48 or 7.17%. However, in 2018, female participation increased, with 101 women or 8.85% of the 1,140 candidates who registered. Despite this, the presence of female candidates continues to receive a positive response from the public, as evidenced by the election of women as regional heads and deputy regional heads. In 2005 and 2010, 24 women were elected, while in 2017, the number dropped to 13 or 5.90%. In 2018, 31 women or 9.06% were elected from 342 candidates. Dompu Regency, of the 224 existing districts, is one of the regions that will hold simultaneous regional elections in 2020. The 2020 regional elections are a new history for Dompu Regency because for the first time there are women running as candidates for Regent and Deputy Regent, namely Hj. Eri Aryani as candidate for Regent and Ika Rizky Veriani as candidate for Deputy Regent. This research aims to analyze the strategy implemented by Hj. Eri Aryani in the 2020 simultaneous regional elections. The method used in this research is descriptive qualitative. The research results show that the Eri-HI pair has not been able to carry out an optimal political strategy.